Apelin administration improves insulin sensitivity in overweight men during hyperinsulinaemic‐euglycaemic clamp. Issue 1 (10th August 2017) - Gourdy, Pierre; Cazals, Laurent; Thalamas, Claire; Sommet, Agnès; Calvas, Fabienne; Galitzky, Monique; Vinel, Claire; Dray, Cédric; Hanaire, Hélène; Castan‐Laurell, Isabelle; Valet, Philippe
Abstract : Aims: Apelin is a recently identified adipokine known to improve glucose tolerance and insulin sensitivity in murine models. This study was dedicated to the proof of concept that apelin administration also enhances insulin sensitivity in humans. Materials and Methods: Healthy overweight men were enrolled in this randomized, double‐blind, placebo‐controlled, cross‐over study that successively considered the efficacy and the tolerance of 2 doses of (pyr1)‐Apelin‐13. A first group of subjects received 9 nmol/kg ( n  = 8) of (pyr1)‐Apelin‐13 and, after examination of safety data, a second group received 30 nmol/kg ( n  = 8). Each volunteer underwent 2 hyperinsulinaemic‐euglycaemic clamps where the basal level of glucose infusion rate (GIR) was measured from the 90th to the 120th minute (level 1). Continuous intravenous administration of apelin or placebo was ongoing for 2 hours and GIR was finally evaluated from the 210th to the 240th minute (level 2). Primary evaluation endpoint was the difference in GIR between level 2 and level 1 (ΔGIR). Results: A slight increase in ΔGIR was observed with the low apelin dose (0.65 ± 0.71 mg/kg/min, P  = .055) whereas the highest dose significantly improved insulin sensitivity (0.82 ± 0.71 mg/kg/min, P  = .033). Cardiovascular monitoring and safety reports did not reveal any side effect of apelin administration. Conclusion: As the first demonstration of the insulin‐sensitizing action of apelin in humans, alongside numerous studies in rodents, this trial confirms that the apelin/APJ pathway should be considered as a new target to design alternative therapeutic strategies to control insulin resistance in type 2 diabetic patients.